2014
DOI: 10.1007/s10803-014-2033-x
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder as Early Neurodevelopmental Disorder: Evidence from the Brain Imaging Abnormalities in 2–3 Years Old Toddlers

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental condition that occurs within the first 3 years of life, which is marked by social skills and communication deficits along with stereotyped repetitive behavior. Although great efforts have been made to clarify the underlying neuroanatomical abnormalities and brain-behavior relationships in adolescents and adults with ASD, literature is still limited in information about the neurobiology of ASD in the early age of life. Brain images of 50 toddlers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
96
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 48 publications
10
96
1
1
Order By: Relevance
“…Seed-based, resting-state functional connectivity between the amygdala and canonical targets is reduced in preschool-aged children with ASD (Shen et al, 2016), consistent with what might be expected given increased amygdala volumes and atypical FA in limbic regions such as the uncinate and the inferior longitudinal fasciculi (Conti et al, 2017; Solso et al, 2016; Wolff et al, 2012; Xiao et al, 2014). A series of studies from Courchesne et al also indicates atypical connectivity in language areas, patterns of which have been associated with measures of receptive and expressive language function (Dinstein et al, 2011; Eyler et al, 2012; Lombardo et al, 2015; Redcay & Courchesne, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…Seed-based, resting-state functional connectivity between the amygdala and canonical targets is reduced in preschool-aged children with ASD (Shen et al, 2016), consistent with what might be expected given increased amygdala volumes and atypical FA in limbic regions such as the uncinate and the inferior longitudinal fasciculi (Conti et al, 2017; Solso et al, 2016; Wolff et al, 2012; Xiao et al, 2014). A series of studies from Courchesne et al also indicates atypical connectivity in language areas, patterns of which have been associated with measures of receptive and expressive language function (Dinstein et al, 2011; Eyler et al, 2012; Lombardo et al, 2015; Redcay & Courchesne, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…To our knowledge, this study is the first to employ a network-based structural connectivity approach to assess brain connectivity differences in toddlers with ASD compared with peers with other developmental disorders (other-DD), as the only previous study using diffusion imaging [Xiao et al, 2014] employed voxel-based analysis, thus focussing on brain regions rather than connections.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the absence of univocal predictive biomarkers, early detection is informed by the presence of a constellation of behavioural signs that show significant overlap between different neurodevelopmental disorders, which makes the discriminative value of early neuropsychological assessments very heterogeneous across studies [Mitchell et al, 2011]. To the best of our knowledge, only one study compared brain diffusion between toddlers with ASD and those with developmental delay, showing higher fractional anisotropy in the corpus callosum, posterior cingulate cortex and limbic lobes in the former [Xiao et al, 2014], while no studies explored differences in structural connectivity. To the best of our knowledge, only one study compared brain diffusion between toddlers with ASD and those with developmental delay, showing higher fractional anisotropy in the corpus callosum, posterior cingulate cortex and limbic lobes in the former [Xiao et al, 2014], while no studies explored differences in structural connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Since autism is a disorder of early neural development (Courchesne et al, 2011; Willsey et al, 2013; Stoner et al, 2014), it is particularly important to examine inter-hemispheric connectivity at very young ages when the behavioral symptoms of autism first emerge (Courchesne et al 2007; Pierce et al 2011). Only a few DTI studies have done so and all have reported that the CC at young ages in autism exhibits abnormally increased FA values (Ben Bashat et al 2007; Weinstein et al 2011; Xiao et al 2014; Travers et al 2015; Solso et al 2016). This finding stands in sharp contrast to findings in mature children, adolescents and adults where nearly every study has reported reduced CC FA values in autism (Barnea-Goraly et al 2004; Alexander et al 2007; Jou et al 2011; Travers et al 2012; Vogan et al 2016).…”
Section: Introductionmentioning
confidence: 99%